2014
DOI: 10.1177/0739986314562928
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Latino Arrest

Abstract: This article examines the impact of Latino nativity and origin on the risk of arrest. Survey data are used to compare the odds of arrest within and between various U.S. race-ethnic groups over one decade. Net of legal, demographic, and social correlates of arrest in teen and young adult samples, Blacks consistently experience higher odds of arrest than other groups. Puerto Rican arrest risk approximates that of Blacks while foreignborn Latinos consistently experienced a lower arrest risk than Whites. This effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Generational differences between rates of JJS involvement among foreign born and U.S. born individuals have been identified. Both Miller 8 and Tapia 9 showed, in a nationally representative sample, that foreign-born Latinx youth (6.9%) have lower rates of JJS involvement than their U.S.-born counterparts (12.6%). Tapia also demonstrated that, between 1998 and 2008, the arrest gap between U.S.-born Latinxs and foreign-born Latinx youth widened significantly, with the rate for U.S.-born Latinxs more than double that of foreign-born Latinxs by 2008.…”
Section: Psychiatric Needs and Behavioral Health Disparitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Generational differences between rates of JJS involvement among foreign born and U.S. born individuals have been identified. Both Miller 8 and Tapia 9 showed, in a nationally representative sample, that foreign-born Latinx youth (6.9%) have lower rates of JJS involvement than their U.S.-born counterparts (12.6%). Tapia also demonstrated that, between 1998 and 2008, the arrest gap between U.S.-born Latinxs and foreign-born Latinx youth widened significantly, with the rate for U.S.-born Latinxs more than double that of foreign-born Latinxs by 2008.…”
Section: Psychiatric Needs and Behavioral Health Disparitiesmentioning
confidence: 97%
“…Further, poor rehabilitative outcomes of incarcerated Latinx youth have been noted 5,33 . For example, Abram and colleagues 4 found that Latinx youth in detention centers with two or more psychiatric disorders (i.e., internalizing, substance use, and behavioral disorders) at baseline were more likely to have a disorder at 4 ½ years of follow-up compared with Latinx youth with only a single psychiatric disorder.…”
Section: Trauma Exposure Among Latinx Youthmentioning
confidence: 99%
“…The effect sizes (e.g., odds ratios and Cohen’s d) of study findings, however, were emphasized as opposed to statistical significance alone. Fifth, methodological constraints have been documented when examining the Latinx population as a homogenous group, such as the lack of generation categorizations (e.g., foreign born vs. U.S. born) and racial identifiers (e.g., White vs Black; Tapia, 2015 ). Further exploration is needed to solidify whether the heterogeneity and intersectionality of the Latinx sample (e.g., Black Latinx and sexual gender minority status) prove to have distinct self-cutting behavior trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study by Barnes et al (2015) of the Add Health survey data showed that 40% of Native Americans, 38% of Blacks, and 29% of Whites had been arrested by young adulthood; however, these authors did not examine arrest prevalence among Hispanic individuals. Other studies have found that inequalities in the likelihood of a self-reported arrest are not explained by differential involvement in offending, gang membership, peer effects, school and family risk factors, socioeconomic status, and neighborhood characteristics (Andersen, 2015;Crutchfield et al, 2012;Mitchell & Caudy, 2015, 2017Stevens & Morash, 2015;Tapia, 2010Tapia, , 2011Tapia, , 2015.…”
Section: Prior Research On Race/ethnicity and Youth Arrestmentioning
confidence: 93%